Pañjāba, rājanītika paridr̥śya aura Hindī kahān - Siṃha, Pushpapāla. (Ātmārāma eṇḍa Saṃsa, 1994)
Short stories based on the present Punjab, India, by contemporary authors.
In Hindi.
Short stories based on the present Punjab, India, by contemporary authors.
Keywords: Hindi fiction / 20th century. / http://id.loc.gov/authorities/subjects/sh2008105615; Short stories, Hindi. / http://id.loc.gov/authorities/subjects/sh85121875; Punjab (India) / Fiction.